Effect of Bio-Based Nano Minerals in Wheat - Hem C. Joshi, Dhruv Mishra, Yashpal Singh, Om Prakash, Preeti Chaturvedi (International Journal of Advanced Science and Technology, 2020)
The present study reports the effect of bio-based nano minerals on morphology and yield of wheat (Triticum Aestivum L.). The experimental pots were filled with sandy clay loam, and had organic carbon (0.72%), available nitrogen (216 kg/ha), available phosphorus (22 kg/ha) and available potassium (133 kg/ha). The treatments were control (Rec. NPK), absolute control, parthenium based bio mineral, neem based bio mineral, FYM based bio mineral, clay based bio mineral and vegetable peel based bio nano mineral. These bio-nano minerals were prepared in the ratio of 2:1(gypsum: biomineral). TEM of bio-nano minerals revealed that the resultant bio-nano mineral was in the range of 5 to 100nm. Pot experiment showed that plant height obtained with neem and FYM based bio nano minerals, were statistically similar with each other. Number of tillers was found maximum with parthenium based nano bio minerals at all growth stages. Dry matter accumulation was found maximum with neem based bio nano minerals. Grain yield, straw yield and biological yield was found maximum under neem based bio nano minerals, which was significantly higher than rest of the treatments. From these experiments, it can be concluded that wheat crop performed better under neem based bio nano minerals.